Calorie Need Estimates - Houtkooper, Linda (College of Agriculture and Life Sciences, University of Arizona (Tucson, AZ), 2006)
2 pp. === The energy content of food is measured in calories. The number of calories, or energy, an athlete needs to maintain weight depends upon: age, body weight, gender, Resting Energy Expenditure (REE) and physical Activity Energy Expenditure (AEE) levels.